Antivinculin antibodies as a marker of irritable bowel syndrome–diarrhea in Egyptian patients. Issue 4 (October 2018) - Bayoumy, Essam; Sabry, Manal; Abdraboh, Naglaa R.
Abstract : Background: Circulating antivinculin antibodies have been used as a marker for irritable bowel syndrome especially the predominant diarrhea (IBS-D) subtype. There is no available data regarding their use as biomarker in diagnosing and follow up the patients of irritable bowel syndrome in the Middle East. We aim to evaluate the use of antivinculin antibodies as a potential diagnostic biomarker in Egyptian patients of IBS-D. Patients and methods: This study was carried out over 9-month duration on 90 individuals, divided into two groups: group 1 included 70 patients with IBS-D, group 2 included 20 healthy volunteers as a normal control group. All participants have been subjected to colonoscopic examination, in addition to measurement of serum levels of selected inflammatory markers and antivinculin antibodies. Results: The serum level of antivinculin antibodies was significantly higher in IBS-D patients in comparison to the normal control group, Moreover, there was a highly significant elevation of the inflammatory markers (erythrocyte sedimentation rate, C-reactive protein, and total leucocyte count) in the IBS-D group. Conclusion: This study recommends the use of antivinculin antibodies as a potential diagnostic biomarker in Egyptian patients with IBS-D with underlying low-grade inflammation as a possible pathogenetic mechanism in IBS.